IDENTIFIKASI CITRA DAUN DENGAN MENGGUNAKAN METODE DEEP LEARNING CONVOLUTIONAL NEURAL NETWORK (CNN) - saiful rahman, aswadul fitri; b, a asni; kurniawan, septian dwi (lembaga Penelitian Universitas Balikpapan, 2019)
In the world of programming, deep learning methods of convolutional neural networks (CNN) may be very rarely heard, because this method was only popular around 2015, and this time I will conduct an experiment using this method, where I will conduct experiments on identification systems leaf image whose application is almost similar to a face recognition system, the leaf image identification system itself consists of detection and classification stages. Both of these stages are done so quickly by humans but it takes a long time for the computer. The application also uses MATLAB 2018a software with the CNN method we can find out the image data classification and can do the process of identifying images properly.